IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING PICTURES MEDIA TO THE SEVENTH GRADE STUDENTS OF SMP NEGERI 21 MEDAN - Turnip, Merry Christina; Rumapea, Linus; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2020)
This thesis discusses about the improving students’ vocabulary mastery by using pictures media to the seventh grade students of SMP Negeri 21 Medan. This study applies pictures, one of media which can be used by the teacher to build students’ mastery of vocabularies. To master the language, vocabulary is important element in learning process. This statement is supported by Thornbury. He said that without vocabulary nothing can be conveyed. This study is a field study in two cycles; each cycle consists of planning, action, observation, and reflection. In collecting data, I used qualitative and quantitative data. The qualitative data are observation sheet, and questionaire and field notes. The qualitative data were collected through observing the teaching learning process, holding the discussion with the teacher, and taking photographs of the teaching learning process. The quantitative data are pre-test and post-test to measure the students’ vocabulary mastery by using pictures media. The instruments for collecting data were observations checklist, field notes, and photographs. This study concludes that the students’ vocabulary mastery is improved by using pictures media. It can be seen from the means score of pre test is 65, and post test is 78. In additional, the implementation pictures media are successful to help the students memorize and understand new words easily.